Prispevek urbane geografije k urbanističnemu planiranju - primer ureditve degradiranega območja Trbovelj - Marot, Naja (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2006)
Two centuries of mining have significantly changed the town of Trbovlje in economic, social and spatial terms. This is especially evident in the south-eastern part of the town. On the basis of general geographical analysis of spatial, demographic and economic development, a query of public opinion and a survey of experts' ideas, with description of successful English urban renewal project we try to find out the most effective model and context of the future development in the area in question.
Keywords: urbana geografija; mesta; degradacija okolja; prenova; sanacija; urbanizem; urbanism; urbanistično planiranje; Trbovlje